Design of a safer approach to intravenous drug infusions: failure mode effects analysis. Issue 4 (2nd August 2004) - Apkon, M; Leonard, J; Probst, L; DeLizio, L; Vitale, R
Abstract : Objectives: A set of standard processes was developed for delivering continuous drug infusions in order to improve (1) patient safety; (2) efficiency in staff workflow; (3) hemodynamic stability during infusion changes, and (4) efficient use of resources. Failure modes effects analysis (FMEA) was used to examine the impact of process changes on the reliability of delivering drug infusions. Setting: An 11 bed multidisciplinary pediatric ICU in the children's hospital of an academic medical center staffed by board certified pediatric intensivists. The hospital uses computerized physician order entry for all medication orders. Methods: A multidisciplinary team characterized key elements of the drug infusion process. The process was enhanced to increase overall reliability and the original and revised processes were compared using FMEA. Resource consumption was estimated by reviewing purchasing and pharmacy records for the calendar year after full implementation of the revised process. Staff satisfaction was evaluated using an anonymous questionnaire administered to staff nurses in the ICU and pediatric residents who had rotated through the ICU. Results: The original process was characterized by six elements: selecting the drug; selecting a dose; selecting an infusion rate; calculating and ordering the infusion; preparing the infusion; programming the infusion pump and delivering the infusion. The following practice changes were introduced: standardizing formulations for all infusions; developing database driven calculators; extending infusion hang times from 24 to 72 hours; changing from bedside preparation by nurses to pharmacy prepared or premanufactured solutions. FMEA showed that the last three elements of the original process had high risk priority numbers (RPNs) of >225 whereas the revised process had no elements with RPNs >100. The combined effect of prolonging infusion hang times, preparation in the pharmacy, and purchasing premanufactured solutions resulted in 1500 fewer infusions prepared by nurses per year. Nursing staff expressed a significant preference and pediatric residents unanimously expressed a strong preference for the revised process. Conclusions: Standardization of infusion delivery reduced the frequency for completing the most unreliable elements of the process and reduced the riskiness of the individual elements. Both contribute to a safer system.